KAJIAN PENGARUH KONTROL ALIRAN TERHADAP KOEFISIEN HAMBAT MODEL KENDARAAN - Boli, Rahmad Hidayat; Rauf, Wawan; Rifal, Moh; Pido, Rifaldo (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
The characteristics of the airflow that is formed around the vehicle body affects the value of the resistance acting on the vehicle. When it reaches the rear edge of the vehicle, the flow undergoes a process of separation. So modification of the vehicle body design that is able to reduce the separation is urgently needed. Flow engineering around the vehicle body can be obtained by modifying the shape which is considered more aerodynamic. Meanwhile, flow engineering can also be obtained through the application of an active control system in areas that are considered to have the potential to initiate flow eddies on the rear side of the vehicle and have a major influence on the formation of flow separation. This research aims to examine the impact of the application of flow control blowing technique on the resistance of the modeled vehicle. The geometric angle of the front wall is determined to be 35°. The research uses a numerical computational approach with a standard k-epsilon as a turbulence model. The upstream velocity applied is 13.9 m/s, while the blowing velocity is set at 0.5 m/s. The research results prove that the application of blowing flow control has succeeded in minimizing the formation of wake structures and has the effect of delaying separation and has succeeded in reducing the aerodynamic drag coefficient to 9.3187%.